Etiologic Framework for the Study of Neurodegenerative Disorders as Well as Vascular and Metabolic Comorbidities on the Grounds of Shared Epidemiologic and Biologic Features - de Pedro-Cuesta, Jesús; Martínez-Martín, Pablo; Rábano, Alberto; Ruiz-Tovar, María; Alcalde-Cabero, Enrique; Calero, Miguel (Frontiers in Aging Neuroscience, 2016)
Background. During the last two decades, protein aggregation at all organismal levels, from viruses to humans, has emerged from a neglected area of protein science to become a central issue in biology and biomedicine. This paper constitutes a risk-based review aimed at supporting an etiologic scenario of selected, sporadic, protein-associated, i.e. conformational, neurodegenerative disorders, and their vascular- and metabolic-associated ailments. Methods. A rationale is adopted, to incorporate selected clinical data and results from animal-model research, complementing epidemiologic evidences reported in two prior papers. Findings. Theory is formulated assuming an underlying conformational transmission mechanism, mediated either by horizontal transfer of mammalian genes coding for specific aggregation-prone proteins, or by xeno-templating between bacterial and host proteins. We build a few population-based and experimentally-testable hypotheses focusing on: 1) non-disposable surgical instruments for sporadic Creutzfeldt-Jakob disease and other rapid progressive neurodegenerative dementia, multiple system atrophy, and motor neuron disease; and, 2) specific bacterial infections such as B. pertussis and E. coli for all forms, but particularly for late-life sporadic conformational, neurodegenerative disorders, type 2 diabetes mellitus, and atherosclerosis where natural protein fibrils present in such organisms as a result of adaptation to the human host induce prion-like mechanisms. Conclusions. Implications for cohort alignment and experimental animal research are discussed and research lines proposed.